Immunological aspects of persistent hepatitis B in children - Harsoyo Notoatmojo (Indonesian Pediatric Society, 2001)
We studied the immunological status of 203 children having persistence Hepatitis B (positive HBsAg) ranging in age from 6 to 14 years in Semarang Municipality. The results of humoral immunity examination (IgM Anti-HBc) showed that all were negative, indicating that they are not in acute phase of hepatitis B infection. Cellular immunity examination, i.e., CMI skin test has shown positive result in 64.9% on persistent and 65.2% in non persistent hepatitis B (p>0.05). T cell examination showed statistically significant difference (p<0.01) between persistenct and non persistent hepatitis B patients, there was is also significant difference (p<0.01) on CD4 cell examination. These findings indicated that there was difference in immunoregulation function and response repression of antivirus between both groups of patients. On the other hand CD4/ CD8 ratio and T cell function showed no significant difference between the two gorups of patients; similarly the specific function of cytotoxic T cell was not significantly difference.